A colorimetric lateral flow assay based on multiplex PCR for the rapid detection of viable Escherichia coli O157:H7 and Salmonella Typhimurium without enrichment. (December 2021) - Kim, Jin-Hee; Oh, Se-Wook
Abstract: Foodborne pathogens are a food safety problem, and there is demand for rapid and sensitive diagnostic methods. Therefore, multiplex PCR-lateral flow assay (mPCR-LFA) with concentration methods was studied for detecting Escherichia coli O157:H7 and Salmonella Typhimurium. To sensitively detect only viable bacteria in cabbage and reduce time required for results, propidium monoazide was used to selectively inhibit DNA amplification and was subjected to filtration and DNA concentration. This increased the sensitivity by 10‒100-fold. E. coli O157:H7 and S . Typhimurium were then simultaneously amplified using mPCR and detected using dual LFA. Our results showed that mPCR-LFA detected 10 2 CFU/25 g and 10 1 CFU/25 g of E. coli O157:H7 and S . Typhimurium in 100 min, respectively. This demonstrated that mPCR-LFA and concentration can potentially be performed without cultural enrichment to detect foodborne pathogens. Highlights: Two-step filtration and DNA concentration were used as concentration methods. The mPCR-LFA was used to amplify and detect the target genes. PMA was used to selectively suppress DNA amplification from dead cells. PMA treatment did not affect sensitivity of the mPCR-LFA assay. Viable target bacteria were rapidly and sensitively detected by PMA-mPCR-LFA.